The PHF11 gene is not associated with asthma or asthma phenotypes in two independent populations. Issue 7 (21st April 2009) - McClenaghan, J; Warrington, N M; Jamrozik, E F; Hui, J; Beilby, J P; Hansen, J; de Klerk, N H; James, A L; Musk, A W; Palmer, L J
Abstract : Background: Numerous areas of the human genome have previously been associated with asthma and asthma-related phenotypes, but few positive findings have been successfully replicated in independent populations. Initial studies have reported strong associations of variants in the plant homeodomain zinc finger protein 11 ( PHF11 ) gene with serum IgE levels, asthma, airway hyper-responsiveness and childhood atopic dermatitis. Objectives: To investigate the association of variants in the PHF11 gene with asthma and associated intermediate phenotypes in two independent Western Australian population-based samples. Methods: A linkage-disequilibrium (LD)-tagging set of 20 single nucleotide polymorphisms (SNPs) was genotyped in PHF11 in two separate populations (total n = 2315), a family-based twin study consisting of 230 families (n = 992 subjects) and a population-based nested case-control study consisting of 617 asthma cases and 706 controls. Information regarding asthma, respiratory physiology, atopy and environmental exposures was collected. Transmission disequilibrium tests, variance components models and generalised linear models were used to test for association between PHF11 SNPs and selected asthma outcomes (including longitudinal change in lung function). Results: After correction for multiple testing, no statistically significant (p<0.05) associations were found between PHF11 and either asthma or total serum IgE levels in either population. No statistically significant associations were found with any other asthma-associated phenotypes in either population. Conclusions: Previously reported associations of PHF11 with asthma outcomes were not replicated in this study. This study suggests that PHF11 is unlikely to contain polymorphic loci that have a major impact on asthma susceptibility in our populations.